Promising Catalytic Systems for CO2 Hydrogenation into CH4: A Review of Recent Studies - M. Carmen Bacariza (Processes, 2020)
The increasing utilization of renewable sources for electricity production turns CO2 methanation into a key process in the future energy context, as this reaction allows storing the temporary renewable electricity surplus in the natural gas network (Power-to-Gas). This kind of chemical reaction requires the use of a catalyst and thus it has gained the attention of many researchers thriving to achieve active, selective and stable materials in a remarkable number of studies. The existing papers published in literature in the past few years about CO2 methanation tackled the catalysts composition and their related performances and mechanisms, which served as a basis for researchers to further extend their in-depth investigations in the reported systems. In summary, the focus was mainly in the enhancement of the synthesized materials that involved the active metal phase (i.e., boosting its dispersion), the different types of solid supports, and the frequent addition of a second metal oxide (usually behaving as a promoter). The current manuscript aims in recapping a huge number of trials and is divided based on the support nature: SiO2, Al2O3, CeO2, ZrO2, MgO, hydrotalcites, carbons and zeolites, and proposes the main properties to be kept for obtaining highly efficient carbon dioxide methanation catalysts.